PENGEMBANGAN MEDIA TEKA-TEKI SILANG UNTUK MEMAHAMI TEKS BAHASA ARAB SISWA KELAS X SMA - Fitri, Iva Nur Haula; Ahsanuddin, Mohammad (Al-Ma‘rifah, 2025)
This research is motivated by the results of observations, that Arabic language learning at Nusantara Islam High School is still dominated by the active role of the teacher. This is because in providing material the teacher only uses teaching materials without any learning media that is able to arouse students' enthusiasm in learning Arabic. This study aims to develop crossword puzzle media and describe its feasibility as an Arabic language learning medium. Researchers used the R&D method with the ADDIE development model. A total of 24 class X SMA Islam Nusantara were used as research subjects. The results of this study were the development of media in the form of an Arabic crossword book whose material consisted of 6 chapters in odd-even semesters and was compiled based on the 2013 curriculum Arabic language package. This crossword media received a very decent category, namely 82% from material experts and 88% from media experts. This product received a very positive response in trials on students with an average score of 89%. Based on these percentages, it can be concluded that the crossword puzzle media for the Arabic text reading skills of class X high school students is stated to be very valid and feasible to use.